2015
DOI: 10.1002/jaal.498
|View full text |Cite
|
Sign up to set email alerts
|

Inverting Instruction in Literacy Methods Courses

Abstract: Three teacher educators who inverted/flipped instruction in their literacy courses describe their experience in this article. Inverted, or flipped, instruction is a blended learning approach that increases opportunities for active engagement in class by moving basic instructor demonstration and presentation outside of class. The authors provide a rationale for inverting instruction and include relevant research that supports it. They also include a sample literacy module before and after inverting it. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For example, regular class time can be used to organize extracurricular programs or book clubs whose meetings and discussions take place online, outside of class time. This type of a blended learning approach provides opportunities for student engagement inside and outside of class (Shaffer, 2015;Zawilinski, Richard, & Henry, 2015). This may help make college students more willing to spend their time reading online and do offline projects so they are engaged in learning in different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, regular class time can be used to organize extracurricular programs or book clubs whose meetings and discussions take place online, outside of class time. This type of a blended learning approach provides opportunities for student engagement inside and outside of class (Shaffer, 2015;Zawilinski, Richard, & Henry, 2015). This may help make college students more willing to spend their time reading online and do offline projects so they are engaged in learning in different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have indicated that traditional science classes do not offer the most effective learning methods for students, although this has been the typical manner in which higher education courses have instructed students during recent years [3,10,23,24]. Learning, however, must not be considered as a mere transfer and delivery of knowledge to learners.…”
Section: Flipped Classroommentioning
confidence: 99%
“…Without the engagement of teachers, any attempt at BL might fail (Christo-Baker, 2004;Graham & Robison, 2007). Studies have thoroughly proven the benefits and effectiveness of BL (Graham, 2006;Osguthorpe & Graham, 2003;Zawilinski et al, 2016), but often neglected the feelings of teachers, the challenges they meet, their difficulties, anxieties and worries before and during the implementation of BL.…”
Section: Introductionmentioning
confidence: 99%